An Analysis of Ideological Square on Joe Biden and Vladimir Putin Speech Related to Russia-Ukraine War - Kauthsar, Abhid Al; Hamzah, Hamzah (Universitas Negeri Padang, 2024)
Critical Discourse Analysis studies of communication in political contexts have scrutinized the use of language by politicians striving to win public opinion related to some topic or conflict. utilizing Teun A. van Dijk's framework for political discourse analysis, this thesis examines discursive devices and ideological squares in four speeches related to the Russia Ukraine conflict in 2022 from president Joe Biden and president Vladimir Putin. The study described in this thesis combines micro-level text analysis focusing on discursive devices and macro-level analysis focusing on the ideology formed by the ideological square that represents